2019
DOI: 10.3748/wjg.v25.i5.608
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intrahepatic sarcomatoid cholangiocarcinoma: Experience from 11 cases within 17 years

Abstract: BACKGROUNDIntrahepatic sarcomatoid chonalgiocarcinoma (s-CCC) is an extremely rare disease, accounting for less than 1% of hepatobiliary system malignancies, and its pathophysiology is not well known. On the hypothesis that its clinical, serologic, or radiologic diagnosis are not fully understood and its prognosis is poor, we investigated the distinguishing features of s-CCC compared with those of intrahepatic bile duct adenocarcinoma [cholangiocellular carcinoma (CCC)] in patients from a single center.AIMTo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
(43 reference statements)
5
35
0
Order By: Relevance
“…In this study, the median OS following surgical resection for iCCA patients (n = 200) was 16.7 months, similar to that in other reports . After controlling for many confounding factors affecting prognosis through PSM analysis, we reached a consistent conclusion with previous studies that the prognosis of iCCA‐SC is significantly worse than that of ordinary iCCA . For iCCA‐SC, there was a lack of characteristic imaging features from preoperative imaging findings, and there was no significant difference in preoperative serum CEA and CA125 levels between the two groups.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, the median OS following surgical resection for iCCA patients (n = 200) was 16.7 months, similar to that in other reports . After controlling for many confounding factors affecting prognosis through PSM analysis, we reached a consistent conclusion with previous studies that the prognosis of iCCA‐SC is significantly worse than that of ordinary iCCA . For iCCA‐SC, there was a lack of characteristic imaging features from preoperative imaging findings, and there was no significant difference in preoperative serum CEA and CA125 levels between the two groups.…”
Section: Discussionsupporting
confidence: 88%
“…For iCCA‐SC, there was a lack of characteristic imaging features from preoperative imaging findings, and there was no significant difference in preoperative serum CEA and CA125 levels between the two groups. The serum CA19‐9 levels in the iCCA‐SC group were even lower than those in the ordinary iCCA group, which is in accordance with the study of Kim et al This indicated that these serum tumor markers might not be sensitive for iCCA‐SC, and the diagnosis of iCCA‐SC remained elusive and largely dependent upon pathological findings . Fortunately, this complex situation did not affect the decision of the surgical treatment and the extent of the resection.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The histogenesis of sarcomatous tissue in cancers, including HCC, has not yet been elucidated. The most widely accepted theory is the conversion theory, which postulates that the sarcomatous element derives from the carcinoma during tumor evolution[ 3 , 9 , 22 - 25 ]. Several recent studies indicate that epithelial-mesenchymal transition is an important mechanism underlying the sarcomatous change, which further confirms the conversion theory[ 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, 9,11,12 serum CA19-9 and carcinoembryonic antigen (CEA) may not be sensitive enough for the diagnosis of S-iCCA. Of note, a low echogenic liver mass on ultrasound showing hypoattenuation and peripheral region enhancement after contrast injection on a computed tomography scan 9 are common characteristics of S-iCCA, similar to ordinary iCCA. 7 Therefore, it may be difficult to distinguish S-iCCA from ordinary iCCA using radiological imaging.…”
Section: Discussionmentioning
confidence: 99%